The Ubiquitin-Conjugating System: Multiple Roles in Viral Replication and Infection - Arianna Calistri; Denis Munegato; Ilaria Carli; Cristina Parolin; Giorgio Palù (Cells, 2014)
Through the combined action of ubiquitinating and deubiquitinating enzymes, conjugation of ubiquitin to a target protein acts as a reversible post-translational modification functionally similar to phosphorylation. Indeed, ubiquitination is more and more recognized as a central process for the fine regulation of many cellular pathways. Due to their nature as obligate intracellular parasites, viruses rely on the most conserved host cell machineries for their own replication. Thus, it is not surprising that members from almost every viral family are challenged by ubiquitin mediated mechanisms in different steps of their life cycle and have evolved in order to by-pass or exploit the cellular ubiquitin conjugating system to maximize their chance to establish a successful infection. In this review we will present several examples of the complex interplay that links viruses and the ubiquitin conjugation machinery, with a special focus on the mechanisms evolved by the human immunodeficiency virus to escape from cellular restriction factors and to exit from infected cells.